Discs and boulders - D. S. Kieffer (2018)
The TBM disc cutters are commonly used to cut hard blocks, however, litte is known regarding mechanisms in highly heterogeneous bouldery ground. Thus, a range of full-scale tests have been performed using a linear cutting machine at the Colorado School of Mines (CSM). In simulating full-scale rock cutting conditions, the Linear Cutting Machine (LCM) at the Earth Mechanics Institute of CSM is used. The LCM is proven effective in developing accurate performance estimates for different cutting tools. Laboratory tests performed on nine boulders included Unconfined Compressive Strength (UCS), Brazilian Tensile Strength (BTS), static elastic constants tests, and triaxial shear tests. The summary test results concentrates on behavioural modes exhibited by boulders embedded in the stiffest and softest sand grout matrices in order to emphasize basic differences with respect to the behaviour of blocks embedded in matrix materials of significantly different strength and stiffness.